1993
DOI: 10.1249/00005768-199307000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The female athlete triad: disordered eating, amenorrhea, osteoporosis

Abstract: Medicine convened a panel of experts and concerned individuals to address an area of growing concern in sports medicine: a triad of disorders observed in adolescent and young adult female athletes. This two-day workshop explored the medical and practical issues surrounding the Triad disorders in the setting of a comprehensive conference format which addressed prevention, screening, risk profiles, diagnostic parameters, training dynamics, treatment, educational gaps, and research needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
153
0
15

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(183 citation statements)
references
References 0 publications
2
153
0
15
Order By: Relevance
“…We, therefore, constructed a pathogenetic model of stress fracture on the basis of studies in the adult literature and the observations of experienced clinicians. The risk factors deemed most important in our model included BMI, dietary intake of calcium and vitamin D, and heredity and were identified, a priori, as covariates to be measured in the study.Even before the American College of Sports Medicine coined the term "female athlete triad" in 1992 to describe the interrelatedness of disordered eating, amenorrhea, and osteoporosis in young female athletes, 17,18 another area of significant interest in women's skeletal health has been menstrual irregularity (MI). 19,20 Studies have inconsistently shown MI to be a risk factor for stress fracture in active adult women, 21-26 but information on menstrual history was not available from the large epidemiologic cohort that we analyzed previously.…”
mentioning
confidence: 99%
“…We, therefore, constructed a pathogenetic model of stress fracture on the basis of studies in the adult literature and the observations of experienced clinicians. The risk factors deemed most important in our model included BMI, dietary intake of calcium and vitamin D, and heredity and were identified, a priori, as covariates to be measured in the study.Even before the American College of Sports Medicine coined the term "female athlete triad" in 1992 to describe the interrelatedness of disordered eating, amenorrhea, and osteoporosis in young female athletes, 17,18 another area of significant interest in women's skeletal health has been menstrual irregularity (MI). 19,20 Studies have inconsistently shown MI to be a risk factor for stress fracture in active adult women, 21-26 but information on menstrual history was not available from the large epidemiologic cohort that we analyzed previously.…”
mentioning
confidence: 99%
“…[13][14][15] This constellation of disordered eating, amenorrhea, and osteoporosis has come to be known as the "female athlete triad," a term coined by the American College of Sports Medicine in 1993. 16,17 To begin to assess which stress fractures may be markers of compromised bone health, one must understand the epidemiology and causes of these injuries. Although stress fractures cause considerable impairment, 2 unfortunately little is known about the prevalence of or risk factors for stress fractures among young women.…”
mentioning
confidence: 99%
“…It is often accompanied with nutrition and menstrual cycle dysfunctions thus constituting a syndrome often called »Female Sports Triad« (12)(13)(14). Functional hypo thalamic amenorrhea (HPA) is a condition charac terized by the absence of menstrual cycle due to suppression of hypothalamic-pituitary-ovarian axis, without the presence of morphological or organic defects (5).…”
Section: Discussionmentioning
confidence: 99%